2003
DOI: 10.1096/fj.03-0708fje
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role of C5a in LPS‐induced IL‐6 production by neutrophils during sepsis

Abstract: Experimental sepsis in rodents occurring after cecal ligation/puncture (CLP) is associated with excessive complement activation and a systemic inflammatory response. The proinflammatory mediator IL-6 has recently been shown to be an important inducer of the C5a receptor (C5aR) during sepsis. We now provide evidence that serum IL-6 production during sepsis in rats was reduced in neutrophil-depleted animals and that absence of C5aR in mice as well as antibody-blockade of C5a in rats significantly reduced serum l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
112
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(124 citation statements)
references
References 26 publications
6
112
2
1
Order By: Relevance
“…However, excessive and unregulated generation of C5a, which impairs contractility as seen in sepsis, results in defective cardiac function (18). Analogous to this would be our studies in sepsis in which low levels of C5a prime neutrophils for enhanced innate immune functions while high levels of C5a cause a loss of MAPK signaling pathways and greatly impaired innate immune function (26).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…However, excessive and unregulated generation of C5a, which impairs contractility as seen in sepsis, results in defective cardiac function (18). Analogous to this would be our studies in sepsis in which low levels of C5a prime neutrophils for enhanced innate immune functions while high levels of C5a cause a loss of MAPK signaling pathways and greatly impaired innate immune function (26).…”
Section: Discussionmentioning
confidence: 69%
“…We have previously reported that C5a plays an important role in enhancing MIF release from neutrophils, which may explain the restored cardiac performance by a blockade of C5a after burn injury (44). Also, we and others have reported that C5a induces the phosphorylation of p38 and other MAPKs as well as the up-regulation of NF-B (17,26). Therefore, the cardioprotective effects seen after a blockade of C5a may be partially due to inhibition of these intracellular signaling pathways.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The effects of binding of C5a or C5a desArg to their receptors depend on the cell type expressing them. C5a is known to have a range of effects on the innate immune cells in particular neutrophils and macrophages: it is a chemoattractant and enhance expression of adhesion molecules on the cells both of which are important to direct the phagocytes from the blood to the site of infection/injury (80,81); the molecule induce phagocytosis and the consecutive oxidative burst to kill the phagocytized microorganisms (64), and it releases enzymes from intracellular granules as well as induces production and release of cytokines (82)(83)(84). The effect of C5aR binding of C5a is most extensively studied while the role of C5L2 is less well understood, although recent studies have indicated both important pro-and anti-inflammatory effects of the C5L2 receptor (85,86).…”
Section: Complement and Inflammationmentioning
confidence: 99%
“…Anaphylatoxins C3a, C4a and C5a are proinflammatory peptides released from the cleavage of their native components following activation of the complement cascade. These molecules induce vascular permeability [2][3][4], smooth muscle contraction [3][4][5], the release of pro-inflammatory cytokines [6][7][8] and white blood cell chemotaxis [9][10][11]. Among anaphylatoxins, C5a is the most potent [4].…”
Section: Introductionmentioning
confidence: 99%